2015
DOI: 10.1016/j.exer.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

ON pathway mutations increase susceptibility to form-deprivation myopia

Abstract: The ON pathway mutation in nob mice is associated with altered refractive development, and an increased susceptibility to form-deprivation (FD) myopia. In this study, we used mGluR6−/− mice, another ON pathway mutant, to determine whether the nob phenotype was due to the Nyx mutation or abnormal ON pathway transmission. Refractive development under a normal visual environment for mGluR6−/− and age-matched wild-type (WT) mice was measured every 2 weeks from 4 to 16 weeks of age. The response to monocular FD fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
74
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 55 publications
16
74
1
Order By: Relevance
“…With partial form deprivation, retinal DOPAC is decreased locally only in the half of the retina that has been deprived (Ohngemach et al, 1997; Stone et al, 2006) and returns to normal after removal of the diffusers in chickens (Pendrak et al, 1997). Retinal DA levels after form deprivation myopia (FDM) are apparently not altered in wild-type mice (Chakraborty et al, 2015b; Park et al, 2014; Wu et al, 2015), indicating a unique emmetropization process or subtle change of DA in mice. Nonetheless, most studies from multiple species support an association between retinal DA alteration and myopia.…”
Section: Effects Of Altered Da Levels On Myopic Eye Growthmentioning
confidence: 99%
“…With partial form deprivation, retinal DOPAC is decreased locally only in the half of the retina that has been deprived (Ohngemach et al, 1997; Stone et al, 2006) and returns to normal after removal of the diffusers in chickens (Pendrak et al, 1997). Retinal DA levels after form deprivation myopia (FDM) are apparently not altered in wild-type mice (Chakraborty et al, 2015b; Park et al, 2014; Wu et al, 2015), indicating a unique emmetropization process or subtle change of DA in mice. Nonetheless, most studies from multiple species support an association between retinal DA alteration and myopia.…”
Section: Effects Of Altered Da Levels On Myopic Eye Growthmentioning
confidence: 99%
“…Previous studies reported that the ON pathway mutation in mGluR6 À/À and nob mice is associated with myopic shift in refractive development, and leads to an increased susceptibility to FD. 34,35 As recoverinþ OFF-BCs constitute a part of the OFF-BCs, further investigation is needed to determine if changes in the OFF pathway also contribute to myopia development.…”
Section: Bl Selectively Activates/(recruits) D1r Signaling In the On mentioning
confidence: 99%
“…33 Genetic knockout studies indicate that nob mice, which have an ON pathway defect are more susceptible to form deprivation (FD). 34,35 However, there are no reports describing which retinal cell types expressing D1R are activated by BL. Such insight is needed to delineate the signaling pathways mediating D1R control of refraction development.…”
mentioning
confidence: 99%
“…Interestingly, in some myopic patients NYX mutations occur without night blindness (Zhang et al 2007, Zhou et al 2015) suggesting that more subtle alterations of ON-BC signal processing that preserve synaptic transmission may nevertheless cause myopia. The connection of ON-BC dysfunction to myopia is also well supported by the animal models where either pharmacological blockade of ON-BC transmission (Crewther et al 1996, Smith et al 1991) or genetic elimination of NYX or mGluR6 (Chakraborty et al 2015, Pardue et al 2008) similarly exacerbate development of refractive error in experimental models of induced myopia. The molecular basis underlying the involvement of the ON-BC signaling cascade remains unclear, although it is speculated that changes in the levels of neurotransmitter dopamine and/or inputs provided by ON-BC light-driven activity may be among key factors connecting mGluR6 signaling with pathways that control axial growth (Chakraborty & Pardue 2015).…”
Section: Deficits In On-bc Signaling At the Nexus Of Human Visual Dismentioning
confidence: 87%